The Relationship Between Stress Levels and Disease Perception in DM-TB Comorbid Patients in Gorontalo City - Husain, Siti Rahma; Zainuddin, Zainuddin; Sartika, Sartika (Medical and Health Journal, 2026)
Diabetes mellitus (DM) and tuberculosis (TB) are chronic diseases that remain major public health problems and frequently occur concurrently as DM–TB comorbidity. This condition not only worsens patients’ physical status but also affects psychological aspects, particularly stress levels and illness perception. Patients living with two chronic diseases simultaneously tend to experience stress due to long-term treatment burdens, complications, and demands for therapeutic adherence. High stress levels may influence how patients perceive their illness, reduce motivation, and shape negative illness perceptions, which can ultimately hinder optimal disease management. This study aims to analyze the relationship between stress level and illness perception among patients with DM–TB comorbidity in Gorontalo City. This study employed a quantitative, cross-sectional design. The sample consisted of patients with DM–TB comorbidity undergoing treatment at several community health centers in Gorontalo City. Stress level was measured using the Perceived Stress Scale (PSS), while illness perception was assessed using the Brief Illness Perception Questionnaire (BIPQ). Data were analyzed using statistical tests to determine the relationship between stress level and illness perception. The results showed that most patients experienced moderate to high stress levels and tended to have negative illness perceptions. Statistical analysis indicated a significant relationship between stress level and illness perception among patients with DM–TB comorbidity. The higher the patients’ stress levels, the more negative their perception of the illness. It can be concluded that psychological aspects play an essential role in the management of patients with DM–TB comorbidity; therefore, health interventions should integrate clinical and psychosocial approaches to improve treatment adherence and patients' quality of life.